Measuring the True Cost of Government Bailout - Cheryl D. Block (Washington University Law Review, 2010)
Government intervention to assist individual businesses and industries during the 2008–2009 economic crisis was extraordinary in variety and scope. Despite official protestations of no more bailout‖ in the Dodd-Frank Wall Street Reform and Consumer Protection Act of 2010, future government interventions are inevitable, should economic circumstances become sufficiently dire. Moreover, even if Congress eliminates overt bailout-type interventions, indirect forms of public bailout are likely to continue. Understandably, taxpayers have been concerned about the cost. A simple tally of dollars authorized or disbursed is wholly inadequate to accurately assess the costs of various interventions. This Article addresses the challenges of providing reasonable budgetary information with respect to different types of bailout expenditures. In addition to looking at costs for the more obvious bailout programs, the analysis explores the special cost estimation challenges for other more covert actions, such as special tax breaks or relief from burdensome regulation, that serve a "bailout" function. The Article also takes issue with the fragmentation of intervention efforts among different "on-budget" and “off-budget” entities and with some of the methodologies used by the government to value assets obtained in its bailout efforts, arguing that decision making about the appropriate allocation of aggregate resources is hampered when some expenditures are “off-budget” altogether and when even “on-budget” agencies use different accounting methods. Finally, the Article calls for transparency and budget accounting for public bailouts accomplished more indirectly through the tax system and other regulatory regimes. Adequate and transparent budget accounting for bailout costs requires greater consistency in valuation and accounting methods, and a more unified presentation of aggregate information in the budget with respect to all government bailout-type activities.
Keywords: Financial services reform; Budget; Financial institutions; Federal aid; Federal aid to financial institutions; Tax credits; Cost accounting; Troubled Asset Relief Program (U.S.)